R2P: a Counter-Genocidal Strategy of Peace? - Loddo, Salvatore (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
Since 2001, the doctrine of the responsibility to protect (R2P) became a new global standard, a norm that reshapes the right to humanitarian intervention by the international community in response to grave international crimes committed by States. This article shows the function of R2P as countergenocidal strategy for peace bringing out the conceptual and moral premises of its emergence and it lays bare, through the Syrian and Iraqi cases of contemporary wars, the paradox between the fundamental commitment to preventing mass violence and the danger to betray this obligation flattening R2’s applications to the new western way of war consistent with the liberal way of peace.